2017
DOI: 10.1111/ijfs.13674
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and immunomodulatory activities of sulphated polysaccharides from purple glutinous rice bran (Oryza sativa L.)

Abstract: This research aimed to extract polysaccharides and improve the property of sulphate-modified purple glutinous rice bran, cv. Kum Doi Saket. The effects of temperature, ratio of sulphur trioxide-trimethylamine (STMA) to sample and reaction times were studied. The results showed that the degree of substitution (DS) of sulphated polysaccharides was 0.01-0.53. Low molecular weight sulphated polysaccharides were obtained, and the functional groups of the sulphated polysaccharides were confirmed using FT-IR. No enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…Surin et al . () also reported that the immunomodulatory activity of sulphated polysaccharides from purple glutinous rice bran ( Oryza sativa L.) was significantly increased by 10%–86% but no enhancement of the antioxidant activity was observed, when compared to the crude polysaccharides. We speculated these discrepancies might be due to a number of reasons, including but not limiting to the chemical composition, structure and conformation of different polysaccharides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surin et al . () also reported that the immunomodulatory activity of sulphated polysaccharides from purple glutinous rice bran ( Oryza sativa L.) was significantly increased by 10%–86% but no enhancement of the antioxidant activity was observed, when compared to the crude polysaccharides. We speculated these discrepancies might be due to a number of reasons, including but not limiting to the chemical composition, structure and conformation of different polysaccharides.…”
Section: Resultsmentioning
confidence: 99%
“…However, some contrary findings showed that lower molecular weight of polysaccharides, from Oryza sativa L. (Surin et al ., ) and from Lactobacillus confusus TISTR 1498 (Surayot et al ., ), led to higher immunomodulatory activity. Moreover, our results also indicated that TPS–FJ exhibited significant higher immunomodulatory activity than TPS–SC, but their hydroxyl radical scavenging activities were similar at the same concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many studies have found that polysaccharides extracted from plants can relieve the oxidative stress through exerting their antioxidation potentials [26,27]. In addition, plant polysaccharide is a natural nontoxic substance with various biological features.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, natural polysaccharides have attracted much attention in the field of biochemistry and pharmacology because of their health benefits such as immune regulation (Li et al, ; Surin, Surayot, Seesuriyachan, You, & Phimolsiripol, ), antitumor (Meng, Liang, & Luo, ; Zhao et al, ), antifatigue (Jia et al, ), antioxidation (Chaouch, Hafsa, Rihouey, Cerf, & Majdoub, ; Mao et al, ), antidiabetes (Liu, Sun, Rao, Su, Li, et al, ), antihyperglycemia, and antihyperlipidemia (Liu, Sun, Rao, Su, & Yang, ). Stigma maydis (corn silk), a by‐product from corn cultivation and processing (Žilić, Janković, Basić, Vančetović, & Maksimović, ), has been used worldwide as a traditional herbal medicine for the treatment of chronic diseases, such as diabetes (Pan et al, ), obesity (Lee et al, ), hypertension (George & Idu, ), and cystitis (Peng, Zhang, & Zhou, ), due to its multiple bioactive components including polysaccharides, flavonoids, steroids, alkaloids, saponins, proteins, volatile oils, tannins, and vitamins (Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%